Chemometric approaches in the evaluation of trace metals in commercially raised tilapia and preliminary health risk assessment of its consumption / Low Kah Hin - Low, Kah Hin (2012)
The aims of this study are to evaluate the presence of trace metals in aquacultural samples using chemometric methods and to assess the safety of their consumption. In this work, chemometric techniques have been utilized to improve the analysis of metal content in commercially raised tilapia. In the method development phase, multivariate calibration techniques involving principal component regression and partial least squares were employed to establish a simple spectrophotometric method for the simultaneous determination of Cu2+, Ni2+ and Zn2+ in water samples in the presence of 1-(2-thiazolylazo)-2-naphthol as chromogenic reagent. In general, no significant difference in analytical performance was observed between the models as both exhibit high reliability. Unfortunately, the proposed alternative did not work well with other sample matrices. Consequently, the use of microwave accelerated reaction system with appropriate reagent mixture for quantitative matrix decomposition and its effective combination with certain determination techniques were then investigated by experimental design. In the preliminary study, fractional factorial design was utilized to evaluate the main effects of addition of HNO3, H2O2, HCl and H2O in microwave assisted digestion of fish muscle certified reference material. Significant losses of analytes via the vessel pressure regulating mechanism were observed, particularly for Hg under the designed condition. In this regard, digestion using a lesser amount sample and reagent was put forward for investigation with two-stage experimental designs. Initially, a Plackett-Burman design was carried out to estimate the main effects of the added reagents and the influence of microwave settings. The most significant microwave parameters were further evaluated by Box–Behnken design, while others were kept constant. The influence of different parameters vary according to the metal element, thus the working conditions for their simultaneous determination were established as a compromise within the optimum region found for each targeted element. Good agreement was observed between measured and certified values. In the assessment phase, the optimized microwave assisted digestion-inductively coupled plasma-mass spectrometry procedure was successfully applied for the determination of trace metal content in muscle, liver and gill tissues of red tilapia (Oreochromis spp) sampled from three different aquaculture sites in Jelebu, Negeri Sembilan. With the aid of pattern recognition techniques such as principal component analysis and its varimax rotation, it is not only possible to visualize the distribution pattern of metals in different organs as well as clustering tendencies of tilapia samples according to production sites but also to identify their corresponding relationships. For safety evaluation, the metal concentrations in the edible muscles were compared with the established legal limits and reasonable maximum exposures were simulated using the Monte Carlo algorithm.